2017
DOI: 10.1001/jama.2017.2841
|View full text |Cite
|
Sign up to set email alerts
|

Association Between US Norepinephrine Shortage and Mortality Among Patients With Septic Shock

Abstract: Among patients with septic shock in US hospitals affected by the 2011 norepinephrine shortage, the most commonly administered alternative vasopressor was phenylephrine. Patients admitted to these hospitals during times of shortage had higher in-hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(136 citation statements)
references
References 27 publications
(47 reference statements)
2
130
0
4
Order By: Relevance
“…In the NICU, no life-threatening consequences of drug shortages have been reported so far. During the 2011–2012 norepinephrine shortage, an association between the drug shortage and mortality due to septic shock was observed in adult patients [11]. …”
Section: Discussionmentioning
confidence: 99%
“…In the NICU, no life-threatening consequences of drug shortages have been reported so far. During the 2011–2012 norepinephrine shortage, an association between the drug shortage and mortality due to septic shock was observed in adult patients [11]. …”
Section: Discussionmentioning
confidence: 99%
“…During norepinephrine shortages from 2008 to 2013 (≥20% decrease from baseline usage), a retrospective cohort study of 26 US hospitals showed an increase in inpatient mortality to 39.6% during the shortage compared with 35.9% with typical norepinephrine use, representing an odds ratio of 1.15 (1.01 to 1.30; P=0.03) 133. Phenylephrine and dopamine were the most common agents used in place of norepinephrine during the shortage.…”
Section: Prevention and Medical Treatmentmentioning
confidence: 99%
“…The selection of the ideal vasopressor in the setting of shock (regardless of AKI status) has been the source of several large scale multicenter trials 103131132133134135. In the setting of SA-AKI, traditional agents such as norepinephrine (noradrenaline), epinephrine, vasopressin, and dopamine, as well as more novel agents such as angiotensin II and levosimendan, have been investigated.…”
Section: Prevention and Medical Treatmentmentioning
confidence: 99%
“…Vasopressin is recommended as an adjunctive agent to norepinephrine to raise mean arterial pressure or to reduce norepinephrine requirements in patients with septic shock . Approximately 30% of adult patients experiencing septic shock received vasopressin in the second quarter of 2013, however, more recent utilization is unknown . In September 2012, Par Pharmaceuticals submitted a New Drug Application to the United States Food and Drug Administration for an intravenous vasopressin product, which was approved in December 2014 .…”
Section: Introductionmentioning
confidence: 99%